A-density in Soft Topological Spaces (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The soft set theory regards one of an important block of the set theory  has real role in various fields of mathematics , because that the soft set theory solved several mathematical problems.Since the general topology depends on the statements of the set theory, as the soft topology depends on the soft set theory as well.       In this study, the concentration would be on building several properties with newest aspects in the soft topological space. this work required going through some basic concepts with the needed definitions as well.